A preliminary study on the effects of star fruit consumption on antioxidant and lipid status in elderly Thai individuals - Leelarungrayub J. (2017)
© 2016 Leelarungrayub et al. Objective: The aims of this preliminary study were to evaluate the antioxidant and lipid status before and after star fruit juice consumption in healthy elderly subjects, and the vitamins in star fruit extracts. Methods: A preliminary designated protocol was performed in 27 elderly individuals with a mean (±SD) age of 69.5±5.3 years, by planning a 2-week control period before 4 weeks of consumption of star fruit twice daily. Oxidative stress parameters such as total antioxidant capacity, glutathione, malondialdehyde, protein hydroperoxide, multivitamins such as l-ascorbic acid (Vit C), retinoic acid (Vit A), and tocopherol (Vit E), and the lipid profile parameters such as cholesterol, triglyceride, high-density lipoprotein-cholesterol (HDL-C) and low-density lipoprotein-cholesterol (LDL-C) were analyzed. Moreover, Vit C, Vit A, and Vit E levels were evaluated in the star fruit extracts during the 4-week period. Results: In the 2-week control period, all parameters showed no statistically significant difference; after 4 weeks of consumption, significant improvement in the antioxidant status was observed with increased total antioxidant capacity and reduced malondialdehyde and protein hydroperoxide levels, as well as significantly increased levels of Vit C and Vit A, when compared to the two-time evaluation during the baseline periods. However, glutathione and Vit E showed no statistical difference. In addition, the HDL-C level was higher and the LDL-C level was significantly lower when compared to both baseline periods. But the levels of triglyceride and cholesterol showed no difference. Vit C and Vit A were identified in small quantities in the star fruit extract. Conclusion: This preliminary study suggested that consumption of star fruit juice twice daily for 1 month improved the elderly people’s antioxidant status and vi tamins, as well as improved the lipoproteins related to Vit C and Vit A in the star fruit extract.